Emergency remote teaching at EWB-UFx during coronavirus pandemic: Coping with (di)stres - Santos, Elaine Maria; Gomes, Rodrigo Belfort (Signo, 2021)
As coronavirus pandemic has spread all over the world, schools and universities needed to reinvent themselves so that their students could be remotely assisted. In this context, this paper aims to present the experiences of English without Borders Program at the Federal University of XXX with Remote Teaching, highlighting the actions related to the planning sessions, as well as the difficulties teachers and coordinators faced and the adjustments that were necessary. The analysis was carried out using the case study methodology, with teachers’ feedback collected from pedagogical meetings and questionnaires sent by e-mail. The remote teaching modality was contrasted with e-learning, and among the conclusions presented, it was evidenced that the initial difficulties with the promotion of interactions among students were reduced when the feeling of community identity built during the classes was perceived. The teacher training process developed to assist scholarship holders in this new educational scenario was also endorsed as a differential of the program, with the indication that sharing experiences with remote education is necessary so that educators can be prepared for a future surrounded for uncertainties.